2001
DOI: 10.1590/s0100-40422001000600006
|View full text |Cite
|
Sign up to set email alerts
|

Deposição eletrolítica catódica e anódica simultâneas para minimizar interferências de cobre e chumbo na determinação espectrofotométrica de cádmio em água e alimentos via reação com Verde de Malaquita e iodeto

Abstract: Keywords: flow spectrophotometry; cadmium; electrolytic precipitation. INTRODUÇÃOCorantes básicos das séries dos trifenilmetanos e complexos inorgânicos aniônicos de cádmio são extremamente utilizados para a determinação de cádmio por espectrofotometria [1][2][3][4] . A reação entre o corante Verde de Malaquita (MG) e os ânions tetraiodocadimato (CdI 4 2-) é uma das reações mais sensíveis para a determinação de traços de cádmio 5 . Uma séria limitação desta reação para a maioria das amostras rotineiramente ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Copper interference was also reported for this colour reaction [14][15][16][17][18]. It was found that, under the optimised conditions for cadmium elimination, copper ions did not interfere at the levels usually found in waters (less than 500 g l −1 ).…”
Section: Evaluation and Elimination Of Interferencesmentioning
confidence: 60%
See 3 more Smart Citations
“…Copper interference was also reported for this colour reaction [14][15][16][17][18]. It was found that, under the optimised conditions for cadmium elimination, copper ions did not interfere at the levels usually found in waters (less than 500 g l −1 ).…”
Section: Evaluation and Elimination Of Interferencesmentioning
confidence: 60%
“…This makes the interference from cadmium ions quite significant, which had to be eliminated some other way. According to some works [14][15][16][17], where pre-concentration of cadmium was performed in anionic resins, addition of NaCl to the sample would complex cadmium cations into negatively charged chloro-complexes that are strongly held on anion-exchangers. Therefore, an option was made to add NaCl to the conditioning buffer, and to include an anionic exchange resin (AG1 X-8) in the manifold; the result of all these procedures allowed to efficiently eliminate cadmium interference.…”
Section: Evaluation and Elimination Of Interferencesmentioning
confidence: 99%
See 2 more Smart Citations